(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the integration of modern technology into the teaching of the Latin language, emphasizing contemporary approaches to engage learners. It covers a range of technological tools, including interactive online platforms, language learning apps, virtual reality tools, and digital textbooks. The annotation highlights the dynamic learning experiences created through these tools, such as gamified elements, adaptive learning systems, and immersive virtual explorations.